The Use of Antibiotics for the Prophylaxis of Spontaneous Bacterial Peritonitis: A Retrospective Review and Quality Improvement Study - Ariana Tagliaferri; Nida Ansari; Gabriel Melki; Yana Cavanagh (GastroHep)
Conclusion: We intend to educate providers on the appropriate time to intervene to reduce mortality and subsequent hospitalizations for those with advanced liver disease.